Staphylococcus aureus: food handler carriers - Raddi, Maria Stella Gonçalves; Leite, Clarice Queico Fujimura; Mendonça, Clara Peckmann (Revista de Saúde Pública, 1988)
Material was collected from the hands and nasal passages of forty-eight food handlers and twenty college students of Araraquara (S. Paulo State, Brazil) and analized in order to evaluate the carrier function with regard to Staphylococcus aureus. The organism discovered in both samples of nine out of the twelve volunteers were of the same S. aureus phage types. The incidence of carriage on the hands was much greater in the handlers' group. These findings demonstrate the potential risk represented by hands in the transmission of food poisoning.